Student support during project-based learning using simulated automated formative feedback: an experimental evaluation - Murtazin, Kristina; Shvets, Oleg; Karu, Karl-Erik; Puusep, Viljam; Vendelin, Jelena; Meeter, Martijn; Piho, Gunnar (Frontiers in Education, 2025)
Project-based learning is widely recognized as an effective pedagogical approach in software engineering education, fostering real-world problem-solving, collaboration, and the integration of theory and practice. However, its scalability is challenged by the resources demanded for individualized feedback, especially in large classes. This pilot study explored the feasibility of simulated automated formative feedback to support student teams in a project-based software engineering course. Eighty-six students participated over 4 weeks, alternating between receiving simulated automated formative feedback emulated by instructors and standard feedback. Weekly surveys assessed perceptions of usefulness and motivation. No statistically significant differences were found between feedback conditions (Cohen's d = 0.16). Students expressed positive attitudes toward the simulated automated formative feedback: 78% agreed it supported their learning goals, and 74% reported it increased motivation. These findings suggest that automated feedback tools may effectively complement instructor support, offering a scalable solution for enhancing formative feedback in project-based learning environments.